Elaboración de pasta de cacao de alta calidad en base a la fermentación con levadura saccharomyces cerevisiae - Tinoco Matamororos, Carlos Hugo (2010)
This research was conducted in St. Agnes Farm, University of Machala, located in the tropical dry forest ecological zone, site development process benefit from the cocoa beans from national Tenguel. And the second qualification phase of the quality of cocoa, was held in the company Cofina, on the road Duran Tambo. Establish the best dose of yeast by the quality of fermented beans. Determine the best cocoa paste according to the organoleptic characteristics based on the fermentation by adding yeast. Were used fresh almonds national cocoa, they were placed in wooden boxes to ferment, during this process used a thermometer, a peachímetro, and was added baker's yeast of the genus Saccharomyces cerevisiae., in the following concentrations: 1, 1.5, 2, 2.5, and 3g. The results obtained in the curing site showed that the fermentation temperature and pH of the almonds did not reach statistically different compared with the control, but the employee of yeast, especially at the 1.5 g and 2g, we obtained better good fermentation conditions expressed in lower rates of Violet at the cotyledons. Concerning the aromas we can say that the presence of astringency was in each treatment due to acetic acid, although not found bitter, chemical aromas, mold, smoke, land and other